Distribusi Kadar Air Tanah Dengan Irigasi Curah Pada Budidaya Tanaman Stevia (Stevia rebaudiana B.): Distribution of Soil Water Content under Sprinkler Irrigation in Stevia (Stevia rebaudiana B.) Cultivation - Achmad Malkan Mudzakir; Cahyoadi Bowo; Petrus Andianto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Sprinkler irrigation emulates rainfall patterns to supply plant water, improving soil conditions and ensuring sustained field performance. This study investigated the impact of sprinkler irrigation on Stevia's Coefficient of Uniformity (CU), soil moisture level, and crop coefficient (Kc). The experiment was conducted in Karangploso Village, Malang Regency, 700 m above sea level. Stevia plants were cultivated using sprinkler irrigation, and their water requirements were assessed by analyzing changes in soil moisture after irrigation. The results showed that sprinkler irrigation significantly increased soil moisture content. At a depth of 0-20 cm, soil moisture increased by an average of 0.135 cm3/cm3 (water depth of 27 mm), while at depths of 20-40 cm and 40-60 cm, the increase was 0.121 cm3/cm3 (24 mm) and 0.065 cm3/cm3 (13 mm), respectively, with a total water depth of 64 mm for 0-60 cm soil depth of 70 mm irrigation event. The crop coefficient (Kc) of Stevia varied during its growth stage, starting from 0.55 in the first week and gradually increasing to 0.57 in the 6th week. The total water requirement for Stevia until harvest at 60 days reached 279.8 mm. This finding emphasize the importance of monitoring and adjusting irrigation practices to ensure optimal growth of Stevia. Sprinkler irrigation effectively increased soil moisture content and determined the appropriate water requirement and Kc value for Stevia cultivation.